A Survey of Nursing Home Physicians to Determine Laboratory Monitoring Adverse Drug Event Alert Preferences - Boyce, R.D.; Perera, S.; Nace, D.A.; Culley, C.M.; Handler, S.M. (Applied Clinical Informatics, 2014)
Objective: We conducted a survey of nursing home physicians to learn about (1) the laboratory value thresholds that clinical event monitors should use to generate alerts about potential adverse drug events (ADEs); (2) the specific information to be included in the alerts; and (3) the communication modality that should be used for communicating them.Methods: Nursing home physician attendees of the 2010 Conference of AMDA: The Society for Post-Acute and Long-Term Care Medicine.Results: A total of 800 surveys were distributed; 565 completed surveys were returned and seven surveys were excluded due to inability to verify that the respondents were physicians (a 70% net valid response rate). Alerting threshold preferences were identified for eight laboratory tests. For example, the majority of respondents selected thresholds of ≥ 5.5 mEq/L for hyperkalemia (63%) and ≤ 3.5 without symptoms for hypokalemia (54%). The majority of surveyed physicians thought alerts should include the complete active medication list, current vital signs, previous value of the triggering lab, medication change in the past 30 days, and medication allergies. Most surveyed physicians felt the best way to communicate an ADE alert was by direct phone/voice communication (64%), followed by email to a mobile device (59%).Conclusions: This survey of nursing home physicians suggests that the majority prefer alerting thresholds that would generally lead to fewer alerts than if widely accepted standardized laboratory ranges were used. It also suggests a subset of information items to include in alerts, and the physicians’ preferred communication modalities. This information might improve the acceptance of clinical event monitoring systems to detect ADEs in the nursing home setting.Citation: Boyce RD, Perera S, Nace DA, Culley CM, Handler SM. A survey of nursing home physicians to determine laboratory monitoring adverse drug event alert preferences. Appl Clin Inf 2014; 5: 895–906http://dx.doi.org/10.4338/ACI-2014-06-RA-0053
Keywords: Nursing homes; therapeutic drug monitoring; clinical decision support systems; adverse drug event